2021
DOI: 10.4103/lungindia.lungindia_63_21
|View full text |Cite
|
Sign up to set email alerts
|

Determining pulmonary function and the associated risk factors among stone quarry workers in a suburban area of Chennai, Tamil Nadu, India

Abstract: Background: Stone quarrying activities generate dust and fine particulate matters of silica and heavy metals. The prolonged exposure to suspended particulates leads to fatal respiratory complications. Occupational pulmonary complications are poorly characterized among quarry workers in Tamil Nadu. Objectives: This study aims to assess pulmonary function and determine the associated risk factors among quarry workers. Materials and Methods: A c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
2
0
Order By: Relevance
“…Similarly, a Brazilian study reported that respiratory symptoms such as cough and illness were mainly associated with smoking 29) . Likewise, an Indian study by Arumugam et al reported that smoking and longer work years in the quarries were associated with airflow blockage among quarry employees 35) . Hence, the present study investigated that continuous exposure to stone dust, smoking habit, and avoiding masks during work was related to respiratory issues.…”
Section: Discussionmentioning
confidence: 95%
“…Similarly, a Brazilian study reported that respiratory symptoms such as cough and illness were mainly associated with smoking 29) . Likewise, an Indian study by Arumugam et al reported that smoking and longer work years in the quarries were associated with airflow blockage among quarry employees 35) . Hence, the present study investigated that continuous exposure to stone dust, smoking habit, and avoiding masks during work was related to respiratory issues.…”
Section: Discussionmentioning
confidence: 95%
“…Duration of exposure and smoking was found to be predisposing factors for a decrease in lung functions, similar to one of the studies done in Tamil Nadu. 23 Duration of exposure as well as smoking was found to be predisposing factors for a decrease in FEV1. After adjusting for smoking, the duration of exposure in years was found to be an independent risk factor for a decrease in FVC, PEFR, and an increase in FEV1/FVC ratio suggesting that the duration of exposure in years is an independent risk factor for the restrictive type of lung disease among the quarry workers.…”
Section: Predictors Of Lung Function Declinementioning
confidence: 94%